2014
DOI: 10.1017/s0266467414000157
|View full text |Cite
|
Sign up to set email alerts
|

Plant selection and avoidance by the Bornean elephant (Elephas maximus borneensis) in tropical forest: does plant recovery rate after herbivory influence food choices?

Abstract: Abstract:The plant vigour hypothesis proposes that herbivores should favour feeding on more vigorously growing plants or plant modules. Similarly, we would expect herbivores to favour plants that regrow vigorously after herbivory. Larger animals, like elephants, may also select plant species relative to their availability and prefer species with larger growth forms in order to meet their intake requirements. The food preferences of the Bornean elephant (Elephas maximus borneensis) in the Lower Kinabatangan Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Additionally, elephants fed more on grasses and bamboos at recursion sites compared to sites they did not return to. Grasses and bamboos are most commonly found in the riverine and open grass habitats along forest margins (English et al, 2014) where elephants spent more time at recursion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, elephants fed more on grasses and bamboos at recursion sites compared to sites they did not return to. Grasses and bamboos are most commonly found in the riverine and open grass habitats along forest margins (English et al, 2014) where elephants spent more time at recursion.…”
Section: Resultsmentioning
confidence: 99%
“…We expected elephants to spend more time at recursion sites compared to non-recursion sites if the former were higher quality, such as those sites containing preferred food plants like grasses and bamboos (English et al, 2014). Additionally, we expected elephants to return to sites at two temporal scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2018, 10, x FOR PEER REVIEW 3 of 21 natural canopy of the lowland portion of the study region is dominated by the plant family Dipterocarpaceae [18], which is not found in the Neotropics. The lowland study sites include a diverse set of substrates in the western portion of the state, including fertile alluvial substrates along the Kinabatangan river [19], sedimentary substrates found in the Danum Valley [20], and fertile alluvial and infertile sandstone substrates in the Sepilok Forest Reserve (Table 1; [21]). The elevation at these lowland sites varies from 15 m to 150 m above sea level (asl).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on nutritional requirements, selective feeding behavior may also vary seasonally (Sukumar 1992). In Borneo, however, where rainfall is common throughout the year, the effect of seasonality is suggested to be less pronounced (MacKinnon et al 1996;English et al 2014). However, the wet tropical forests of Borneo are characterized by irregular mast fruiting events.…”
Section: Quality As a Determinant Factormentioning
confidence: 99%